2009
DOI: 10.1590/s0103-84782009000400042
|View full text |Cite
|
Sign up to set email alerts
|

Extração de ecdisterona em raízes de ginseng brasileiro

Abstract: Este estudo teve como objetivo otimizar a extração de ecdisterona em raízes de ginseng brasileiro. Primeiramente, para se avaliar a eficiência do solvente extrator, amostras de raízes dois acessos (BRA e JB-UFSM) de P. glomerata foram extraídas em Soxhlet com metanol e clorofórmio, separadamente, durante 4 horas. No segundo ensaio, com o intuito de se escolher o método extrator, a extração foi conduzida em Soxhlet e em ultrassom, utilizando metanol como solvente. Em P. tuberosa, as amostras foram extraídas com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 3 publications
1
6
0
2
Order By: Relevance
“…Crude extract were obtained from five methods of extraction: maceration (Neto et al, 2005) percolation (Farmacopéia Brasileira, 1988) turbolyse (De-Paris et al, 2000) reflux (Gosmann et al, 2003) and Soxhlet method (Flores et al, 2009) using three different mixture of solvents, ethanol:water (90:10 v/v), (80:20 v/v) and (50:50 v/v). For the preparation of extracts, used 10 g of P. glomerata triturated and the extract was filtered, the organic solvent was removed under "vacuum" and lyophilized.…”
Section: Crude Extractsmentioning
confidence: 99%
“…Crude extract were obtained from five methods of extraction: maceration (Neto et al, 2005) percolation (Farmacopéia Brasileira, 1988) turbolyse (De-Paris et al, 2000) reflux (Gosmann et al, 2003) and Soxhlet method (Flores et al, 2009) using three different mixture of solvents, ethanol:water (90:10 v/v), (80:20 v/v) and (50:50 v/v). For the preparation of extracts, used 10 g of P. glomerata triturated and the extract was filtered, the organic solvent was removed under "vacuum" and lyophilized.…”
Section: Crude Extractsmentioning
confidence: 99%
“…Plants of both P. glomerata genotypes showed a high survival rate during the acclimatization phase (Table 2) and a good adaptation to the environmental conditions over the 2 yr of field culture. In a recent study, Flores et al (2009a) studied the impact of two cytokinins (benzylaminopurine and thidiazuron) on the micropropagation of P. glomerata and observed that the addition of these growth regulators was not effective for this species. Thus, the multiplication of Brazilian ginseng by means of nodal segments on MS medium without growth regulators (Nicoloso et al 2001) has proven to be a suitable method to obtain a large number of homogeneous plants with high phenotypical quality.…”
Section: Resultsmentioning
confidence: 99%
“…Stem segments (about 5 cm long) of P. glomerata and P. tuberosa isolated from fieldgrown plants were disinfected by: immersion in 70% (v/v) ethanol solution for 10 s; followed by 10 min immersion, with agitation, in 1.0% sodium hypochlorite (v/v) containing two drops of commercial detergent per 100 ml solution; and lastly, in 0.1% (w/v) HgCl 2 solutions for 5 min, and then rinsed five times in sterile, distilled water. Disinfected nodal segments (1 cm long microcuttings) were transferred into glass culture tubes (25-150 mm) containing 10 ml of the solidified medium of Murashige and Skoog (MS) (Murashige and Skoog, 1962), supplemented with 100 mg l −1 myo-inositol, 30 gl −1 sucrose, and 6 gl −1 agar (Merck), according to Nicoloso et al (2001) for P. glomerata and Flores et al (2006) for P. tuberosa. The pH was adjusted to 5.9, and the medium was autoclaved at 121°C and 1.15 kg cm −2 for 20 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations